Evaluasi Pembelajaran Bahasa Arab dengan Metode Ceramah di Kelas II SDIT Majlis Tafsir Al-Qur’an Surakarta - Muti’ah Salma Fitria (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2022)
This research discusses Arabic language learning in class II A at SDIT Majlis Tafsir Al-Qur’an Surakarta, where several problems have been identified, including: 1) The lecture method is less effective in Arabic language learning, 2) Students struggle to concentrate during Arabic lessons, 3) The lecture method tends to be boring if not combined with other methods. Regarding Arabic language learning using the lecture method, the researcher aims to address the following topics: 1) The lecture method in Arabic language learning, 2) Evaluation of Arabic language learning, 3) Teacher strategies in following up on the results of the evaluation. The purpose of this research is to understand Arabic language learning using the lecture method, the evaluation process, and the teacher’s strategies in following up on the evaluation results of Arabic language learning using the lecture method in class II A at SDIT Majlis Tafsir Al-Qur’an Surakarta. This research uses a qualitative approach with a descriptive method. The data collection techniques used are interviews, observation, and documentation. The research applies Miles and Huberman’s data analysis model, which includes data reduction, data presentation, and data verification. Furthermore, technique triangulation is employed by comparing Arabic language learning data from interviews, observations, and documentation. The research results show that: 1) Arabic language learning with the lecture method is less effective for second-grade students because they tend to get bored and lose concentration during learning activities. 2) During the mid-semester assessment, student scores were quite good because the teacher provided study guides to help students prepare before the exam. 3)To make classroom learning more active, the teacher modified the Arabic learning method from lecture to taqlid (imitation), where the teacher reads the vocabulary and the students repeat what the teacher has read. In addition to the taqlid method, the teacher also assigns tasks to students so they can review the material that has been taught.